Prevalence of Demodex spp among alcohol-dependent patients - Mehmet Kokaçya; Özlem Kaya; Sibel Elmacıoğlu; Ümit Çöpoğlu (Cukurova Medical Journal, 2016)
Purpose: Demodex folliculorum and Demodex brevis are common ectoparasites found in humans and live on the pilosebaceous glands and hair follicles especially on the facial region. Chronic alcohol consumption can weaken immune system and cause more severe infections. Demodex spp is assumed to be more common in alcohol-dependent patients due to partial suppression of immune system and lack of good self-care. The present study aims to investigate the prevalence of Demodex spp. ectoparasite in alcohol-dependent patients.Material and Methods: In the study, 24 patients with a diagnosis of alcohol dependence and 24 healthy control subjects were subjected to standard superficial skin biopsy technique to determine Demodex spp.Results: In 37.5% of alcohol-dependent patients and 4.1% of control subjects Demodex spp. were found positive. Considering the prevalence of Demodex spp, a significant difference was found between alcohol-dependent patients and control subjects.Conclusion: Demodex spp. are more common in alcohol-dependent patients due conditions of reduced self-care and immunosuppression. Demodex parasites should be considered in alcohol-dependent patients with skin lesions, especially on the face, and should to be treated if needed.